Recent Progress in Medicinal Plants, Volume 30: Drug Plants IV
Attention is again focusing on natural sources for finding new lead pharmaceutical compounds as multi-drug resistant strains of infectious disease agents continue to emerge. The vast chemical diversity of medicinal plants is a promising source of lead compounds that is relatively unexplored and the investigation of traditional medicinal plants is a valuable tool for targeting potentially active species. Based on this rationale, the present volume provides 19 research and review articles contributed by eminent scientists from far and wide including Brazil, Colombia, India, Italy, Japan, Malaysia, Nigeria, U.S.A. and Zimbabwe, with a view to bring the recent scientific data to the attention of international scientific community.Some interesting contributions included are:- Reviews on medicinal properties and use of Lippia alba, Bixa orellana, Silphium spp- Wasabia japonica, Abutilon indicum, Psidium guajava, Swertia chirata, Vernonia cinerea and Inula racemosa- Ethnophar-macological uses of Silphium species recorded by native American tribes- Investigations on Amburana cearensis for its antifungal, antibacterial and vasorelaxant effects on CNS- Review on antifertility drugs- Effect of NPK inorganic fertilizers on Gongronema latifolium- Therapeutic plants possessing contraceptive activities in males- Medicinal and economic potential of Seabuck Thorn (Hippophae spp.)- Immunomodulatory effect of Propolis and Gene expression in the seed development of Castor (Ricinus communis)The chapter on Plant extracts as anti-inflammatory components of diet has special significance. These studies have demonstrated that plants have potential medicinal properties to fight against many present-day diseases and conditions.The findings presented would serve as basic material for further work in developing new phyto-therapeutics. The volume has been addressed to phytochemists, pharmacologists, microbiologists, biotechnologists, medical scientists and other researchers engaged in the search of natural products.